How is the Students’ Sustainability Literacy of Junior High Schools in West Java? - Indarini Dwi Pursitasari; Anna Permanasari; Bibin Rubini; Mohamad Iqbal Suriansyah; Annisa Nurramadhani; Toru Matsumoto; Indriyani Rachman (Journal of Natural Science and Integration, 2026)
This research aims to investigate junior high school students’ sustainability literacy in science learning at environmentally based schools and non-environmentally based schools. This research is quantitative and uses a survey method. The participants are 902 students from three non-environmentally oriented school-based junior high schools and three environmentally oriented school-based junior high schools in West Java. Research data were gathered via a survey questionnaire comprising 25 closed-ended statements and 2 open-ended questions, both of which were valid and reliable. Data analysis of closed statements using the RASCH model by categorizing sustainability literacy using a logit value person (LVP) design. The data analysis of open-ended questions uses Voyant Tools, a website that can digitally read and analyze text. The results showed that students' sustainability literacy in both types of schools was moderate, with averages of 77.2 and 76.9. The highest scoring aspect is awareness of environmentally friendly practices. In contrast, the lowest aspect is waste management habits, and the aspect that students in environmentally school-based settings have, with lower levels than in non-environmentally school-based settings, is environmental action and advocacy for sustainable practices. This research highlighted that junior high school students’ sustainability literacy profiles are still in the moderate category across both school categories and need improvement. Keywords: sustainability literacy; junior high school; environmentally based school; sains learning